Chemotactic self-organization captures the dynamics of mammalian hair follicle patterning - Muhamet Ibrahimi; Ebrahim Jahanbakhsh; Athanasia C. Tzika; Michel C. Milinkovitch (Proceedings of the National Academy of Sciences, 2026)
The spatial patterning of mammalian hair follicle precursors in embryonic skin is most commonly studied in the laboratory mouse ( Mus musculus ), where new follicles form equidistantly from preexisting ones in successive waves. This simple geometric rule has been effectively described as emerging from an expansion-induction process. However, such a description is incompatible with more recent developmental data indicating instead that scale, feather, and hair placodes self-organize through reaction–diffusion–chemotaxis cell interactions involving epidermal and dermal signaling. Here, we suggest that the chemotactic component of this framework suffices to describe the dynamics of placode insertion in two mammalian species that exhibit drastically different patterns. More specifically, we investigate a continuum dynamical model capturing interactions between motile dermal mesenchymal cells and an epidermal chemoattractant, embedded in a two-dimensional, isotropically expanding domain representing the growing embryonic skin. Through numerical simulations, mathematical analysis, and comparison to experimental developmental data, we first show that the chemotaxis model gives rise to the effective geometric rule that initially justified the development of the expansion-induction model in the laboratory mouse. Second, we show that the strikingly regular hair placode pattern in the spiny mouse ( Acomys dimidiatus )—with long-range order, specific orientation and anisotropies—is not generated by an expansion-induction mechanism, but is recapitulated by an anisotropic chemotaxis model combined with experimentally observed anisotropic growth. Overall, our findings reveal that variation in the chemotactic component of the corresponding self-organizational system might be a key determinant of interspecific differences in hair placode patterning dynamics and resulting spatial organizations.